2022
DOI: 10.2113/2022/6226445
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Influence of Inclination Angle and Moisture Content on Mechanical Properties and Microcrack Fracture of Coal Specimens

Abstract: Waterproof coal pillar in the underground reservoir is affected significantly by inclination loads and water erosion. Comprehensive understanding of the influence of moisture content and inclination angle on the mechanics properties and microfracture behavior of coal specimens plays an important role for revealing the instability mechanism of waterproof coal pillar. In this paper, a new modified combined compression and shear test (MC-CAST) system was firstly developed for achieving the specimen inclined loadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
2
0
1
Order By: Relevance
“…Experimental research is an important method for studying waterproof coal pillars (Chen et al 2022b). Currently, experimental investigations on waterproof coal pillars primarily focus on the weakening effects of water content on the mechanical parameters of coal samples (Yao et al 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental research is an important method for studying waterproof coal pillars (Chen et al 2022b). Currently, experimental investigations on waterproof coal pillars primarily focus on the weakening effects of water content on the mechanical parameters of coal samples (Yao et al 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [8] analyzed the water inrush mechanism qualitatively and quantitatively. Through acoustic emission (AE) technology and scanning electron microscope (SEM), Chen et al [9] analyzed the mechanical and micro-fracture behavior of water-bearing coal samples. It was concluded that the coal pillar should be prevented from being subjected to inclined load and water erosion to avoid water inrush accidents.…”
Section: Introductionmentioning
confidence: 99%
“…Как показывает опыт, экспериментальные и натурные методы [1,2,3,4] определения напряженнодеформированного состояния целиков не в состоянии решить данную проблему. Единственно возможным вариантом является математическое моделирование, позволяющее определить напряженное состояние в целиках, что позволит прогнозировать их устойчивость.…”
Section: подземные работыunclassified